Risk factors for development of severe respiratory failure in newborns of 37-week gestational age - P. I. Mironov; E. Z. Il'ina; T. V. Saubanova; A. A. Greshilov (Вестник анестезиологии и реаниматологии, 2019)
The aim was to determine the risk factors for severe respiratory failure in newborns of 37-week gestational age.Methods. The study was designed as retrospective, controlled, non-randomized, and single-center. 640 patients corresponded the criteria of inclusion and exclusion. 7 (1.1%) children died. Depending on the gestational age (GA), patients were divided into two groups. The main group (n = 279) included newborns with GA of 37 weeks. The comparison group (n = 361) consisted of newborns with GA of 34‒36 weeks. Both groups of children received comparable critical care and had similar settings of initial artificial pulmonary ventilation. The software of BioStat was used for statistical processing. Results. Patients of the main group had initially higher pressure in the right ventricle, they were in need of noninvasive ventilator more often (χ2 = 4.23; p = 0.05), and pulmonary hemorrhage were also more frequent in them (χ2 = 9.608; p = 0.02). It was mostly newborns delivered by cesarean section who developed respiratory problems. A uterine scar in a pregnant woman made a significant risk factor for severe respiratory failure in patients of the main group (OR ‒ 1.99).Conclusion. Severe respiratory failure in newborns with gestational age at 37 weeks develops with intrauterine growth retardation, the main risk factor of which is the presence of a scar on the uterus.